Osteoblast response to porous titanium and biomimetic surface: In vitro analysis - Prado, Renata Falchete do [UNESP]; de Oliveira, Fernanda Saraiva [UNESP]; Nascimento, Rodrigo Dias [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; Cairo, Carlos Alberto Alves (Elsevier B. V., 2015)
This study analyzed the behavior of human osteoblasts cultured on porous titanium specimens, with and without biomimetic treatment, compared to dense titanium. The experiment had seven groups: Group 1: cells cultured on polystyrene of culture plate wells; Group 2: cells cultured on dense titanium specimen; Group 3: specimen with 33.79% of pores; Group 4: 41.79% of pores; Groups 5, 6 and 7: specimens similar to groups 2, 3 and 4, yet with biomimetic treatment. Real time-polymerase chain reaction with reverse transcription of the following genes was performed: prostaglandin E2 synthase, integrin β1, osterix, Runx2, Interleukin 6, macrophage colony stimulating factor, apolipoprotein E and others. The study achieved data on cell adhesion, growth and viability, total protein content, alkaline phosphatase activity and quantity of mineralized nodule formations. Data were statistically evaluated. Adherent cells and alkaline phosphatase activity were similar in titanium specimens, regardless of the groups. Biomimetic treatment reduced the total protein activity and the viability of tested cells. Most tested genes had statistically similar expression in all groups. The tested porosities did not cause alterations in osteoblast behavior and the biomimetic treatment impaired the biocompatibility of titanium causing cytotoxicity.
Keywords: Biocompatibility; Gene expression; Hydroxyapatite; Osteoblasts; Titanium